India in the second space age of interplanetary connectivity - Giri, Chaitanya (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This volume discusses the emergence of space exploration as a new pivot of the global space economy in the decade of 2020s. Space exploration and human spaceflight will soon become vital strategic initiatives in the imminent second space age, evolving from scientific pursuits to mega-economic projects. As the scope of international cooperation in space forays into soft science diplomacy, the second space age opens opportunities for India to mount its space program as an ambitious yet conscientious, proficient, and cordial player in the global space economy. This book, -- Explores imminent trends in space exploration and interplanetary connectivity plans, their returns to the global economy of the future, and impact on the global astropolitical order; -- Analyses the techno-economic significance of India's space exploration by reviewing the legal, ethical and philosophical challenges; the limits of global space exploration policies; and the economic lacunae for the astropolitical gains; -- Examines the transformational trio of Chandrayaan, Mangalyaan and Gaganyaan; dawn of the second space age; interplanetary connectivity projects; besides discussing the viability of humans becoming an interplanetary species. Part of The Gateway House Guide to India in the 2020s series, this topical volume will be useful for scholars and researchers of international relations, geopolitics, foreign policy, space policy, South Asian studies, strategic studies, and international trade.
"Routledge Focus"
Keywords: Astronautics -- India; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General